Independensi dan Kompetensi Auditor Terhadap Kualitas Audit Dengan Fee Audit Sebagai Variabel Moderasi - Fatah Yasin, Eko; Muawanah, Umi; Rosidi (Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2021)
Abstract: The study was conducted to determine empirical evidence of audit fees as a moderating variable for the independence and competence of auditors on audit quality. This study uses a quantitative approach using explanatory research type. The population consisted of 80 auditors in the Surabaya area. The research sample was 55 auditors with a sampling technique in the form of judgment sampling. Data collection using a questionnaire. To test the feasibility of the research instrument, the validity and reliability tests were carried out. Data were analyzed using multiple linear regression. The results show that auditor independence has a significant positive effect on audit quality, auditor competence has a significant positive effect on audit quality, audit fees strengthen the effect of auditor independence on audit quality and audit fees strengthen the effect of auditor competence on audit quality. Sampling is only at the Public Accounting Firm in Surabaya. Keywords: Independence, competence, audit quality, audit fees